Utilization Of the Internet of Things to Improve the Quality of Services in Sub-Districts/Villages in Indonesia - Hendri Syahputra; Samuel Indrayana; Rudy Irwansyah; Joice Soraya; Mesak Yandri Masela (Jurnal Teknologi dan Manajemen Industri Terapan, 2022)
The implementation of the Internet of Things (IoT) at the smallest government levels, such as sub-districts and villages, is key to digital transformation towards Smart Villages in Indonesia. This study aims to analyze the use of IoT technology to improve the efficiency and transparency of public services in sub-district areas. Using a qualitative approach and a literature review, this article explores how smart sensors, cloud-based data management systems, and self-service applications can reduce bureaucratic delays. The analysis shows that IoT integration can speed up administrative processing times by up to 40% and significantly increase the public satisfaction index. However, challenges such as digital infrastructure gaps and technological literacy in rural areas remain major obstacles. This study recommends collaboration between central and regional governments in standardizing IoT infrastructure and creating inclusive, responsive public services that meet citizens' needs in the industry 4.0 era.